Collaboration Meeting with Hardex Sdn. Bhd. - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 1 July 2021 - A Short Creative Video Competition program discussion in collaboration with Hardex company was held through virtual meeting.